If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -2(3a + 1) = 2(3a + -2) Reorder the terms: 14 + -2(1 + 3a) = 2(3a + -2) 14 + (1 * -2 + 3a * -2) = 2(3a + -2) 14 + (-2 + -6a) = 2(3a + -2) Combine like terms: 14 + -2 = 12 12 + -6a = 2(3a + -2) Reorder the terms: 12 + -6a = 2(-2 + 3a) 12 + -6a = (-2 * 2 + 3a * 2) 12 + -6a = (-4 + 6a) Solving 12 + -6a = -4 + 6a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6a' to each side of the equation. 12 + -6a + -6a = -4 + 6a + -6a Combine like terms: -6a + -6a = -12a 12 + -12a = -4 + 6a + -6a Combine like terms: 6a + -6a = 0 12 + -12a = -4 + 0 12 + -12a = -4 Add '-12' to each side of the equation. 12 + -12 + -12a = -4 + -12 Combine like terms: 12 + -12 = 0 0 + -12a = -4 + -12 -12a = -4 + -12 Combine like terms: -4 + -12 = -16 -12a = -16 Divide each side by '-12'. a = 1.333333333 Simplifying a = 1.333333333
| 7(5cx+y)=34cx-8y | | 3(4x-1.3)=5x-3.9 | | 2x^2+50x-600=0 | | 10x+2-4x-8=2x-18 | | 12(x+5)=13+2 | | -59=5+8 | | 2x^2-11=19 | | -0.9x+5.32=-0.5x+0.52 | | -9-6k=15 | | 2c^2-16c=0 | | Y=4+3(0) | | 5t-13-8t=-20-33t-5 | | 5+3=y | | 6x+8=8x+11 | | 10x-7=5x-5 | | (1/2)x=8 | | (8x)=(2x+23) | | 5-2n=8n-(-4n) | | 5x-2x+21= | | (X)=(3x-10) | | X+X+25=75 | | 64=3x^2 | | 500x-0.69=700x+0.29 | | 8x/3-x=x/6-7/2 | | Y=4+3(-4) | | -6.4=128.0 | | 12x+2y=-48 | | 3.1x-37=2.1x+8 | | Y=-2+3(4) | | 1.8x+1-2.8x=4 | | Y=-2+3(3) | | (((2y^0)*(2xy^0))/(-xy^4))^-4 |